2016
DOI: 10.1089/brain.2016.0437
|View full text |Cite
|
Sign up to set email alerts
|

Increased Modularity of Resting State Networks Supports Improved Narrative Production in Aphasia Recovery

Abstract: The networks that emerge in the analysis of resting state functional magnetic resonance imaging (rsfMRI) data are believed to reflect the intrinsic organization of the brain. One key property of such complex biological networks is modularity, a measure of community structure. This topological characteristic changes in neurological disease and recovery. Nineteen subjects with language disorders after stroke (aphasia) underwent neuroimaging and behavioral assessment at multiple time points before (baseline) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
57
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(62 citation statements)
references
References 43 publications
4
57
1
Order By: Relevance
“…Both of these changes are consistent with a reduction in network modularity, which has been observed in stroke patients, even in the unaffected hemisphere (Gratton, Nomura, Pérez, & D’Esposito, 2012). A recent study of aphasia patients found that improved narrative production following therapy correlated with an improvement in modularity of resting state networks (Duncan & Small, 2016). …”
Section: Introductionmentioning
confidence: 99%
“…Both of these changes are consistent with a reduction in network modularity, which has been observed in stroke patients, even in the unaffected hemisphere (Gratton, Nomura, Pérez, & D’Esposito, 2012). A recent study of aphasia patients found that improved narrative production following therapy correlated with an improvement in modularity of resting state networks (Duncan & Small, 2016). …”
Section: Introductionmentioning
confidence: 99%
“…This is likely because performance does not depend solely on the “missing” parts of the brain, but also on the structural and functional integrity of the remaining tissue, which can support the functional reorganization of language processes [Carter et al, ; Corbetta et al, ; Crofts et al, ; Rorden and Karnath, ; Saur et al, ; Siegel et al, ; Turkeltaub et al, ; Wu et al, ]. Consequently, proper prediction of aphasia scores requires the integration of multiple neuroimaging modalities, each describing a different property, spanning from lesion maps to structural disconnections, and from pairwise connections to network properties [Carter et al, ; Crofts et al, ; Duncan and Small, ; Grefkes and Fink, ].…”
Section: Introductionmentioning
confidence: 99%
“…As noted above, Duncan and Small (2016) indicated that improvement in untrained narrative language samples was associated with increased network modularity from pre- to post-treatment. For a treatment designed using CATE principles,Sandberg et al (2015) found increased connectivity of left superior medial frontal and right inferior frontal cortices to other cortical nodes for participants whose training generalized from abstract to semantically related concrete words.…”
Section: Neural Plasticity and Generalizationmentioning
confidence: 71%
“…The nature and timing of the next wave of paradigm shifts is difficult to foresee, though many of them undoubtedly will relate to the ever evolving technosphere around us. A more modest, and perhaps achievable, objective would be to point to a few current trends from the current state of affairs that likely will accelerate: (a) With respect to neuroimaging and neural plasticity, imaging neural systems and their connectivity has found its way from the cognitive neuroscience laboratory into the neurocognitive rehabilitation literature (e.g., Duncan & Small, 2016), and this trend will only accelerate in the search to understand the neural underpinnings of this kind of rehabilitation. (b) Multi-modality neuroimaging research has already occurred in the neurocognitive rehabilitation arena.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation